A salience hypothesis of stress in PTSD. (21st November 2021) - Chakraborty, Prabahan; Chattarji, Sumantra; Jeanneteau, Freddy
Abstract: Attention to key features of contexts and things is a necessary tool for all organisms. Detecting these salient features of cues, or simply, salience, can also be affected by exposure to traumatic stress, as has been widely reported in individuals suffering from post‐traumatic stress disorder (PTSD). Interestingly, similar observations have been robustly replicated across many animal models of stress as well. By using evidence from such rodent stress paradigms, in the present review, we explore PTSD through the lens of salience processing. In this context, we propose that interaction between the neurotrophin brain‐derived neurotrophic factor (BDNF) and glucocorticoids determines the long lasting cellular and behavioural consequences of stress salience. We also describe the dual effect of glucocorticoid therapy in the amelioration of PTSD symptoms. Finally, by integrating in vivo observations at multiple scales of plasticity, we propose a unifying hypothesis that pivots on a crucial role of glucocorticoid signalling in dynamically orchestrating stress salience. Abstract : A disruption of glucocorticoid function due to trauma leads to disrupted processing of salience in PTSD. This can be corrected by additional exogenous intervention with glucocorticoids after trauma.